If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12d + -84 = 0 Reorder the terms: -84 + 12d = 0 Solving -84 + 12d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '84' to each side of the equation. -84 + 84 + 12d = 0 + 84 Combine like terms: -84 + 84 = 0 0 + 12d = 0 + 84 12d = 0 + 84 Combine like terms: 0 + 84 = 84 12d = 84 Divide each side by '12'. d = 7 Simplifying d = 7
| -6+15g=9+15g | | 8y-30=34 | | 3(y+2)=y+24 | | 2x+15=14-x | | (-8x+2y)(-4x+4y)= | | c=(3x+y-4)*5-5y+3 | | 5-15t=-15t-14 | | 4+14x=2x-8+12x | | -18n+6n-3=5-12n | | 965.3616=87.92*r^2+62.17*r | | -6y-1=-9y+2 | | 7x-5+3x=75 | | -6-10v=-10v-6 | | w^2-2w=-67 | | -4m+7=7-4m | | 3(p-3)=24 | | -3z-10=-z+10 | | -8r-9=-8r | | 2(x-3)+5(1-x)=2 | | 11m-66-17= | | 5k-9=-9+5k | | 40(9+7x)+3-5x=17 | | 965.3616=87.92*r^2+6.28*r*9.9 | | 2-2u=-2u+2 | | -2x+-1+x= | | 8(j-4)=2(4j-3) | | 0=5b-5b | | 5(5a+2)-4a=0 | | 6x-10=5x-11 | | -2p=-p+6 | | 8(j-4)=3(4j-16) | | 5t-45= |